New directions in family law reform in the Caribbean - Robinson, Tracy S. (2000)
Examines recent development in Caribbean family law reform such as: Antigua and Barbuda Divorce Act 1997; the Belize Families and Children Act 1998; and the Trinidad and Tobago Cohabitational Relationships Act 1998 and Community Mediation Act 1998.